POTENSI ACTINOMYCETES SEBAGAI SUMBER SENYAWA BIOAKTIF ANTIBIOTIK DARI KAWASAN KARST BANTIMURUNG, SULAWESI SELATAN - A.M, Kumalasari; Fathurahman R, Nur; Nur R., Muhamad (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
The purpose of the research is to reveal the bioactive substance which is produced byActynomycetes bacteria in order to inhibit the growth of tested organism.The data were collected in several steps consisting of sampling and isolating theActinomycetes which was done in the main research area (Bantimurung), screening theobtained isolates, characterizing the obtained isolates, and determining of the growth curveof Actinomycetes, and the last was growth inhibitory test.The research finding was the inhibitory potential was actually different from one fungiisolate to other isolates treated to C.albicans, S.Aureus, dan E.Coli. It was probably becauseof the different sensitivity of each tested pathogenic microorganism to the antibioticsubstance.Keywords: Antibiotic, Karstic, Actinomycetes